Deforestation alters species interactions. Issue 2 (24th March 2023) - Howes, Benjamin; González‐Suárez, Manuela; Jensen, Henrik Jeldtoft; Anjos, Luiz dos; Develey, Pedro F.; Hatfield, Jack H.; Morante‐Filho, José Carlos; Uezu, Alexandre; Banks‐Leite, Cristina
Abstract: Interspecific interactions are a major determinant of stability in ecological communities and are known to vary with biotic and abiotic conditions. Deforestation is the primary driver of the ongoing sixth mass extinction, yet its effect on species interactions remains largely unexplored. We investigate how deforestation affects species interactions using a complex systems model and a co‐occurrence dataset of 363 bird species, observed across 134 sites, from 5 regions across the Brazilian Atlantic Forest totalling 27, 226 interactions. Both theoretical and empirical results show that interspecific interactions vary non‐monotonically with forest cover and are more positive than average in areas with higher forest cover, and to a lesser extent in highly deforested areas. Observed differences in interactions reflect both species turnover and changes in pairwise interactions. Our results point to changes in stability across the gradient of deforestation that may lead to varying community resilience to environmental perturbations. Key Interdisciplinary Aspects: Species interactions are expected to vary due to the biological, chemical and physical changes caused by deforestation on their local environment. We use a mathematical complex systems approach, as well as ecological data, to show that species interactions are more positive in highly forested areas. We propose that the alteration of species interactions caused by deforestation will affect the stability of communities and their resilience to future perturbations (e.g. climate change). Abstract :